The Effect Of Parkour Exercises On Some Physical And Motor Abilities And Movement Performance In Artistic Gymnastics For Female Students (Journal of the College of Basic Education, 2024)
The research aimed to design a training program using parkour exercises and to know its effect on some motor and physical abilities and the performance of motor sentences in artistic gymnastics for female students, and to test its hypotheses and to achieve the objectives of the research. The researcher used the experimental method by using an experimental design for two groups, experimental and control, using a pre- and post-measurement method. The research community included Of the female students of the first stage in the College of Basic Education, Department of Physical Education and Sports Sciences, who numbered (40) for the academic year (2023/2024), the researcher deliberately selected the research sample from among the female students, who numbered (10), and they were randomly divided into two groups based on Each of them was (5) for female students, one experimental and the other a control, and the most important results were that the proposed training program using parkour exercises has a positive effect on both motor and physical abilities (agility, coordination, flexibility, muscular ability, transitional speed). The proposed training program using parkour exercises Parkour led to an improvement in the level of motor skill performance among female students.